Fibrolamellar liver cancer: the modern concept - E. Yu. Antonova; V. V. Breder; E. A. Moroz; K. K. Laktionov; I. A. Dzhanyan; A. Yu. Volkov (Медицинский совет, 2020)
Fibrolamellar hepatocellular carcinoma (FLC) is a relatively rare primary liver tumor of unknown etiology (chronic infections with hepatitis B or C viruses, chronic alcohol poisoning, cirrhosis of the liver), which occurs mainly in the young population. FLK is more often diagnosed already at common stages due to the absence of pronounced clinical manifestations in patients for a long time. In pathomorphological diagnostics, FLC is a cluster of large polygonal eosinophilic cells with a clearly defined vesicular nucleus, surrounded by abundant growths of lamellar fibrosis. In most cases, collagen fibers are arranged in parallel strands; in metastatic tumors, collagen fibers can be arranged haphazardly (the so-called “tangled fibers”).For many years, attempts have been made to identify reliable markers for the detection and differential diagnosis of FLC and to determine the cause of tumors in young patients, and the molecular mechanisms of FLC carcinogenesis have been studied. In 2014 during the full transcriptome analysis of FLC samples, the chimeric transcript DNAJB1PRKACA was discovered, which is formed as a result of deletion of a section of chromosome 19 with a size of 400 thousand nucleotide pairs and leads to the fusion of two genes, which Is found in most FLC samples. Surgery is the only curative treatment of this tumor type and radical method of treating the disease. Given that lymph node involvement is an important prognostic factor, complete periportal lymphadenectomy should be performed as part of radical surgery for patients with FLK. The role and possibilities of locoregional and drug-based treatment methods are not fully clear, and the search for effective treatment regimens and potential targets specific to this form of HCR is urgent. Studies show conflicting results for different chemotherapy regimens and the use of targeted therapy. The literature describes isolated clinical cases of successful use of immunotherapy in patients with PD-L1-expressing tumors. The most important condition for successful treatment is an in-depth study of the molecular mechanisms of FLC carcinogenesis. This review presents current data on epidemiology, classification, clinico-morphological, molecular and genetic aspects, as well as some diagnostic features and FLC treatment modalities.